PEMANFAATAN LIMBAH LUMPUR PENGOLAHAN AIR SEBAGAI BAHAN PEMBUATAN BATU BATA - Mizwar, Andy; Amalia, Siti Rizki (Bumi Lestari Journal of Environment, 2012)
Bricks manufactured from water treatment sludge were investigated on clay mixing and1000ÚC firing temperature. Results of tests indicated that the sludge proportion were thekey factor determining the brick quality. Increasing the sludge content results in an increaseof brick water absorption and a decrease of brick shrinkage, compressive strength, anddensity. With up to 10% sludge added to the bricks, all of testing parameter met therequirements of the Indonesian National Standards (SNI 15-2094-2000). Toxic characteristicleaching procedure (TCLP) tests of brick also showed that the metal leaching level is lowand met the requirements of Indonesian government regulations (PP No. 85 Tahun 1999).
Keywords: brick; compressive strength; SNI 15-2094-2000; water treatment sludge